Is rare cancer care organized at national health system level? Multiple case study in six EU countries - Prades Joan; Trama Annalisa; Casali Paolo G; Emile Jean-FRancois; Gaspar Nathalie; Janavicius Ramunas; Janciauskiene Rrasa; Karjalainen Sakari; Kopeckova Katerina; Pylkkänen Liisa; Svoboda Marek; Borras Joseph M (OXFORD UNIV PRESS, 2025)
Background: As a system of European Reference Networks (ERNs) emerges, the differences in quality of care for patients with rare cancers may increase at national level. We aimed to elucidate the processes and healthcare planning principles through which the reference centres (RCs) for rare cancers are embedded in national health systems.
Methods: We used a multiple case-study design based on the experiences of Czechia, Finland, France, Italy, Lithuania and Spain. Using sarcoma as an example of rare cancer, 52 semi-structured interviews were conducted during on-site visits, including a multidisciplinary group of professionals, Ministry of Health professionals, patient representatives and European policymakers.
Results: The comparative analysis showed substantial heterogeneity in the processes for formalizing RCs' status and in their levels of integration in the different health systems, but two models (centre-based and the network-based) can be envisaged at national level. RCs for rare cancers were legally established only in France and Spain. Expert clinicians cooperate in a structured way, using network mechanisms, in France and Italy, and these countries, plus Finland and Lithuania, had a referral system to facilitate patients' access from non-expert centres to RCs. Seven key healthcare planning principles in instituting RCs at the national level were identified.
Conclusions: The conditions governing patient access to treatment centres-whether RCs or not-are decided at the national level. It is advisable to progressively align the European and national levels so that the RCs that participate in the ERNs also play a significant role at the national level.